Relationship Between Workload and Nurse Performance in the Inpatient Ward of Nene Mallomo Hospital - Tinta, Yulis; Ekasari, Ekasari; Muhtar, Arlina; Risal, Abd.; Armadi, Armadi (PSPP JOURNALS, 2024)
Workload is an effort to detail the components and target volume of work in a certain time unit and result unit. Performance is the appearance of the results of personnel's work both in quantity and quality in an organization. The ratio of nursing staff needs is based on the number of patients treated still not meeting the standard. On the one hand, it is said that in providing services to patients, quality must be improved. The type of research used is